An In-Depth Analysis of Choice of Law Rules in Consumer Contracts: A Focus on the African Continental Free Trade Area - Fiattor, Ethel (Journal of Law, Society and Development)
Choice of law is a perplexing concept due to the importance of party autonomy, the diversity of connecting factors, and the variety of different contractual issues. The problem of choosing a governing law is complicated in consumer contracts by industrialised mechanisms depriving consumers of negotiation rights. The core mandate of the African Continental Free Trade Area (AfCFTA) is to establish a single market for goods and services associated with the free movement of legal persons for economic integration. This objective requires a harmonised consumer protection policy to resolve the diverse consumer protection regimes applicable in state parties within AfCFTA member states. This policy should provide suitable consumer protection mechanisms generally and in the context of choice of law specifically. Implementing a draft competition policy bestows a legitimate mandate on the AfCFTA to negotiate a continental framework on consumer protection as both fields of law complement each other to safeguard consumer rights in cross-border trade. This article argues the dynamics of providing adequate choice of law rules on consumer contracts to inform suitable mechanisms on consumer interest within the AfCFTA. The article discusses the abuse of choice of law clauses in consumer contracts, affecting consumers’ rights in cross-border contracts within the AfCFTA. It suggests a harmonised consumer protection policy to regulate and mitigate these clauses. The article also examines trends in Global North jurisdictions like the European Union to inform a context-specific institutional framework for the AfCFTA’s choice of law rules.